Infrastructure Assessment And Design for Al-Samou’ Down Tow - Tahboub, Abdalazez; Jabari, Ahmad; Nofal, Haya (My University, 2017)
The down town of Al-Samou’ is located in the center of the town, which has a great historical and archaeological value, as it is many archeological sites and Canaanitemonuments. This area faces many problems in itsinfrastructure such as roads, buildings and networks, this has become worse in the last years, so study and assess for the current situation ofthe existing infrastructure , problems analysis and designing for some parts of infrastructure must be fixed to keep down town in good status . The current project concern in studying and evaluating the main parts of infrastructure in the most important area in Al-Samou’downtown , then analyze the problems and solving it through making a design forthe most importantpart of infrastructure. After making an evaluation of Al-Samou’ down town,the study shows that the absence of waste water collection system is the worst problem which must solve through making design for waste water collection system using gravity system to minimize the cost , the system is contain three main trunks , seven sub main trunks and one lateral trunks .
CD 30200, NUMBER OF PAGES 66 , مساحة 3/2017 , in the store
Keywords: Roads, Storm Water Runoff, Building, Sewer CAD, Al-Samou’ , old building